Effect of Galvanic Coupling Between Stainless Steel and Carbon Steel on the Rupture of Passive Film - Chebahi, N.; Nedjar, Ratiba; Bounoughaz, M.; Rebbah, Houria (Asian Journal of Chemistry, 2010)
The galvanic corrosion can appear on heterogeneous coupling such as the contact of stainless steel and carbon steel. Carbon steel is then anodic compared to stainless steel. We studied the influence of surface ratio (stainless steel/carbon steel) on galvanic corrosion in a chloride solution. The potentiodynamic polarization and morphological observations in scanning electronic microscopy have been used for this study. The conclusions of present study can be summarized as follows: (a) the corrosion potential and rate of combined materials are between those of materials taken only. The potential of stainless steel is higher than that of carbon steel (b) the micrographics of the working electrode reveal that the generated phenomenon is a galvanic phenomenon of corrosion.